4‐Hydroxy‐2‐nonenal attenuates 8‐oxoguanine DNA glycosylase 1 activity. Issue 12 (6th July 2020) - Pan, Guodong; Deshpande, Mandar; Pang, Haiyan; Stemmer, Paul M.; Carruthers, Nicholas J.; Shearn, Colin T.; Backos, Donald S.; Palaniyandi, Suresh S.
Abstract: Elevated cellular oxidative stress and oxidative DNA damage are key contributors to impaired cardiac function in diabetes. During chronic inflammation, reactive oxygen species (ROS)‐induced lipid peroxidation results in the formation of reactive aldehydes, foremost of which is 4‐hydroxy‐2‐nonenal (4HNE). 4HNE forms covalent adducts with proteins, negatively impacting cellular protein function. During conditions of elevated oxidative stress, oxidative DNA damage such as modification by 8‐hydroxydeoxyguanosine (8OHdG) is repaired by 8‐oxoguanine glycosylase‐1 (OGG‐1). Based on these facts, we hypothesized that 4HNE forms adducts with OGG‐1 inhibiting its activity, and thus, increases the levels of 8OHG in diabetic heart tissues. To test our hypothesis, we evaluated OGG‐1 activity, 8OHG and 4HNE in the hearts of leptin receptor deficient db / db mice, a type‐2 diabetic model. We also treated the recombinant OGG‐1 with 4HNE to measure direct adduction. We found decreased OGG‐1 activity ( P > .05), increased 8OHG ( P > .05) and increased 4HNE adducts ( P > .05) along with low aldehyde dehydrogenase‐2 activity ( P > .05). The increased colocalization of OGG‐1 and 4HNE in cardiomyocytes suggest 4HNE adduction on OGG‐1. Furthermore, colocalization of 8OHG and OGG‐1 with mitochondrial markers TOM 20 and aconitase, respectively, indicated significant levels of oxidatively‐induced mtDNA damage and implicated a role for mitochondrial OGG‐1 function. In vitro exposure of recombinant OGG‐1 (rOGG‐1) with increasing concentrations of 4HNE resulted in a concentration‐dependent decrease in OGG‐1 activity. Mass spectral analysis of trypsin digests of 4HNE‐treated rOGG‐1 identified 4HNE adducts on C28, C75, C163, H179, H237, C241, K249, H270, and H282. In silico molecular modeling of 4HNE‐K249 OGG‐1 and 4HNE‐H270 OGG‐1 mechanistically supported 4HNE‐mediated enzymatic inhibition of OGG‐1. In conclusion, these data support the hypothesis that inhibition of OGG‐1 by direct modification by 4HNE contributes to decreased OGG‐1 activity and increased 8OHG‐modified DNA that are present in the diabetic heart. Abstract : This report explains that mtOGG‐1 activity is reduced by 4HNE adduction, which increased 8OHG in the mitochondria of diabetic cardiac tissue.